ASPEK PSIKOLOGIS DAN METODOLOGIS DALAM PEMBELAJARAN BAHASA ARAB DI MI AL-AMIN PEJERUK KOTA MATARAM - Syahrul Izomi (Ibtida'iy : Jurnal Prodi PGMI, 2023)
"Students are individuals with all the attributes inherent to them. Therefore, monitoring and evaluation of educational institutions, especially for tracking students, are necessary. Therefore, this research aims to explain the problems and solutions in the psychological and methodological aspects of Arabic language learning at MI Al-Amin Pejeruk Mataram. The research overview is to identify, describe, and analyze various methodologies for teaching Arabic language in relation to students' psychological aspects. This research uses a qualitative approach. The reason for the choice of this research method and technique is because the primary activity of this research is to describe learning activities that require a description. Data collection techniques include interviews, observations, and documentation. The research results show several facts supported by the majority of learning that is adapted to the material and follows the curriculum applied in the classroom. Educators ask students to continuously use 'mufrodat'.